Prescribing Patterns and Utilization Trends of Anti-Asthmatic Drugs in Children: An Observational Study in a Pediatric Population: Prescribing Patterns and Utilization Trends of Anti-Asthmatic Drugs - Bahalkani, Ubedullah; Shah, Iftikhar Haider; Khuhro, Asif Ali; Kumar, Pardeep; Bharo, Mumtaz Ali; Zaki, Muhammad (Pakistan Journal of Health Sciences, 2025)
Pediatric asthma occurs as a common chronic respiratory illness. Objectives: To evaluate the prescribing patterns and utilization trends of anti-asthmatic medications in pediatric patients, assessing adherence, appropriateness, and factors influencing drug selection. Methods: This observational study investigated pediatric asthma patients over six months, collecting data from 160 children aged 4–10 years. The data was obtained from pediatric asthma patients about their demographic information, alongside their asthma severity status and medication choices, and delivery methods. Data were analyzed by SPSS version 21.0. Chi-square test evaluated all associations between variables. Results: The study included 160 patients, with 31.3% of them within the age range of 8–9 years, and males represented 56.3% of the group. Urban residents (62.5%) were more affected. The bronchodilator medicine Salbutamol received the highest prescription rate (56.3%), and Budesonide held the position as the most commonly chosen corticosteroid (31.3%). The usage rate of Montelukast reached 45.0% while Theophylline's prescription was limited to just 11.3% of patients. The primary choice of medication delivery involved nebulization for 53.1% of patients, whereas 31.3% received inhalers and 15.6% had oral administration. The standard treatment for mild asthma patients involved Montelukast at a rate of 37.5% and Budesonide treated 34.4% of moderate cases, while severe asthma patients received Salbutamol + Ipratropium in 28.1% of cases. Conclusions: Prescribing patterns in pediatric asthma were closely linked to disease severity, with increased use of nebulizers and combination therapies in severe cases. Tailored, severity-based management can enhance treatment outcomes and promote rational drug use in children.